Os “dinossauros” como marcas patêmicas: a relação museu/escola na comunidade rural de Peirópolis, município de Uberaba/MG - FERREIRA, Carmen Lucia (2016)
This research had as a starting point for its studies and reflections the quest for understanding the relationship between the "Dinosaur Museum" and the "Escola Municipal Frederico Peiró", both located in the Rural community of Peirópolis, municipality of Uberaba, Minas Gerais, Brazil. Our research takes advantage of the unique peculiarities of the rural community of Peirópolis, since the Museum is located right in front of the school, a mere 100 meters away. And to study this relationship, we seek to understand the vision of a group of students in fifth grade (Elementary School) at the School mentioned, through the Grupo Focal methodology. To this end, we analyzed the words and drawings produced by this group of students on the topic investigated, that is, how the students and the School itself perceive the Dinosaur Museum. To analyze the students‘ words and graphical representations (drawings) on the theme "Dinosaurs", represented in parts of dinosaurs (fossils and replicas) exposed at the museum, we used the theoretical contribution of discursive process analysis, specifically the studies by Patrick Charaudeau about the records and pathematic marks related to this topic. This study allowed us to check the dynamism of the theme "dinosaurs" as a pathematic mark which has been powered by the cinema since 1914. The words and drawings of the subjects surveyed pointed to the interest and fascination that the topic brings to children. On the other hand, the survey also points to the lack of a systematic and planned use of the Museum by the School, that is, the analysis of the students' words indicated that most of the knowledge that the subjects investigated hold on the topic comes from movies, and/or sporadic visits to the Museum. The lack of or little use of the Museum by the School shows us that, although students hold fragmented knowledge on the topic (which is normal, because they are still developing), they don't completely correlate as a characteristic of the Museum a place that belongs to them, nor as their own living space. However, the research signaled to the wide range of information that can be used by the School for the integral formation of the students. Finally, we were able to verify that the School and the Museum may forge closer ties and that such spaces can complement not only the development of students' learning, but, above all, implement proposals involving the School, the Museum and the rural community of Peirópolis, which can contribute to the intellectual development of the students and teacher training through the construction of new teaching methodologies, as well as the strengthening and dissemination of scientific and tourist potential of the entire community investigated. In this sense, we will be building the main aspects and factors required for the construction of the identity of learners in the context of their local reality.